Letter (copy) : Raincoats for Spain - Tewson, Vincent
028-0134-001 HVT/FC/358. Secretary's. 21st December, 1936 Mr. W. Schevenels, The International Federation of Trade Unions, 9, Avenue D'Orsay, Paris, VIIIe. Dear Mr. Schevenels. RAINCOATS FOR SPAIN. I have been asked by Sir Walter to let you know that we have completed arrangements for the placing in hand of an order for 5,000 double-textured, double-breasted raincoats with fleecy linings to be delivered at a cost of 5/6d. per garment. We are in touch with the Commercial Attache at the Spanish Embassy in London in regard to shipping arrangements, and hope that half the consignment will be ready for despatch by boat from South Wales at the end of December and that the remaining half of the order will be completed in time for despatch by boat from South Wales on January 6th. As you will notice the price is exceptionally favourable and has been made possible through the assistance of the buyers of the Co-operative Wholesale Society in this country. Yours sincerely, Assistant Secretary. 292/946/28/134